RELIGIOUS MODERATION IN KAMPOENG PERCIK COMMUNITY - Prayogo, Tonny Ilham (Islamuna: Jurnal Studi Islam, 2025)
ABSTRACT The study of religious moderation is pivotal in countering the growing threats of extremism, radicalism, and intolerance that disrupt social cohesion and communal harmony. This research explores the internalization of inclusive religious values as practiced in Kampoeng Percik, a community recognized for its interfaith harmony. Employing a qualitative literature review approach grounded in the sociology of religion, data were gathered through observation, interviews, and documentation. The study reveals three key findings: (1) the implementation of inclusive religious education fostering tolerance and moderation; (2) the practice of justice and fairness in interreligious interactions; and (3) the emergence of a moderate ethos that supports interfaith coexistence. Additionally, the research identifies contemporary challenges posed by digitalization and highlights adaptive strategies undertaken by the Kampoeng Percik community. These findings contribute to the discourse on religious moderation by offering a community-based model of inclusivism that is resilient in the face of socioreligious tension and technological disruption. ABSTRAK Kajian tentang moderasi beragama menjadi hal yang krusial dalam menangkal maraknya ancaman ekstremisme, radikalisme, dan intoleransi yang mengganggu kohesi sosial serta harmoni antar komunitas. Penelitian ini mengkaji internalisasi nilai-nilai keagamaan yang inklusif sebagaimana diterapkan oleh masyarakat Kampoeng Percik, yang dikenal atas keharmonisan antarumat beragama. Dengan menggunakan pendekatan literatur review kualitatif dalam kerangka sosiologi agama, data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan tiga temuan utama: (1) penerapan pendidikan agama yang inklusif yang menanamkan nilai moderasi dan toleransi; (2) praktik keadilan dalam interaksi antarumat beragama; dan (3) munculnya etos moderat yang mendorong kehidupan lintas agama yang harmonis. Selain itu, penelitian ini mengidentifikasi tantangan era digitalisasi serta strategi adaptif yang dilakukan oleh masyarakat Kampoeng Percik. Temuan ini memberikan kontribusi terhadap wacana moderasi beragama melalui model komunitas berbasis inklusivisme yang tangguh dalam menghadapi ketegangan sosial-keagamaan dan disrupsi teknologi.